HUBUNGAN TINGKAT PENDIDIKAN DENGAN PREFERENSI PEMILIHAN MODEL BISNIS TOKO ONLINE - Thomas Yuni Gunarto (Universitas Gunadarma, 2015)
Online store as part of E-commerce from day to day growing rapidly, and increasingly organized according to the grouping's business model E-commerce. Visitors E-commerce demographically divided into several groups one of which is the level of education. This study aims to determine the effect of education on elections E-commerce business model as measured by the number of visits to the site. Correlation analysis was used to measure the effect of the general level of education tersebut.Secara have a strong influence on the selection of E-commerce business model. Keywords: Shop online , E-commerce, business models